Asbestos Exposure of Chrysotile Miners and Millers in Balangero, Italy. Issue 6 (2nd May 2020) - Silvestri, Stefano; Ferrante, Daniela; Giovannini, Andrea; Grassi, Francesco; Carofalo, Stefania; Ferrara, Rita; Magnani, Corrado; Mirabelli, Dario
Abstract: The largest chrysotile mine in Western Europe was active in Balangero (Italy) from 1917 to 1990. We quantitatively assessed exposure to asbestos in the framework of a cohort study on mortality of Balangero miners and millers. Using documents filed at the Italian State Archive we reconstructed the job-histories of cohort members. The concentration of asbestos fibres by work-area was derived from industrial hygiene surveys since 1968 and monitoring programs since 1975. Earlier exposures had been estimated based on the experimental reconstruction of past working conditions. In the mine concentrations of about 20 fibres per millilitre (f/ml) were initially present, decreasing to 5 in the mid-1950s and to <1 in late 1970s. In milling areas higher levels were present and did not fall below 1 f/ml until the mid-1980s. Cumulative exposure of cohort members, as the sum over their job-history of their year- and area-specific exposures, were <10 fibre/millilitre years (f/ml-y) in 18% of workers, 10–100 in 32%, 100–1000 in 37%, and >1000 in 13%. Compared with recently published estimates for the Russian chrysotile mine in Asbest, fibre concentrations in Balangero were higher during the 1950s and 1960s. Such difference may be partly accounted for by difficulties in converting dust measurements to fibre concentrations in the Russian study and the need to rely on the experimental reconstruction of exposures before 1968 in our study.